Tabu językowe w badaniach ukrainistycznych – dorobek i perspektywy - Stępnik-Szeptyńska, Jadwiga (Studia Ukrainica Posnaniensia, 2025)
This article presents the state of research on language taboo and euphemisms in Ukrainian. It gives an overview and brief discussions of selected works, enabling the main tendencies to be recognized and illustrated. The distinction between so-called primitive and modern taboo is included. Publications dealing with language taboo and euphemisms in folklore as well as literature and translation are treated separately. The conclusion points to some research gaps and outlines future perspectives, such as a dictionary of taboo words and euphemisms in standard Ukrainian, a synthesis of dialectal data, and a historical account.